Ecology and characterization of Streptomyces species associated with common scab disease conducive and biofumigated soils in South Africa - Gouws, Reinette (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhDAgric)--Stellenbosch University, 2013.